Cyclic Metalated Nitriles: Stereoselective Cyclizations to cis- and trans-Hydrindanes, Decalins, and Bicyclo[4.3.0]undecanes - Fleming, Fraser F. (2008)
Metalated nitriles are nucleophilic chameleons whose precise identity is determined by the nature of the metal, the solvent, the temperature, and the structure of the nitrile. The review surveys the different structural types and their cyclization trajectories to show how to selectively tune the metalated nitrile geometry for stereoselective cyclizations to a variety of cis or trans hydrindanes, decalins, and bicyclo[4.3.0]undecanes.